Can There be Short-Period Deterministic Cycles When People are Long Lived? - Aiyagari, S. Rao (Quarterly Journal of Economics, 1989)
This paper considers whether short-period deterministic cycles can exist in a class of stationary overlapping generations models with long- (but finite-) lived agents. It shows that if agents discount the future positively, then as life spans get large, nonmonetary cycles will disappear. Further, neither constant monetary steady states nor stationary monetary cycles can exist. It also shows that if agents discount the future negatively, then there are robust examples in which constant monetary steady states as well as stationary monetary cycles (with undiminished amplitude) can occur no matter how long agents live.